Electric Field Induced Biomimetic Transmembrane Electron Transport Using Carbon Nanotube Porins. Issue 32 (16th July 2021) - Hicks, Jacqueline M.; Yao, Yun‐Chiao; Barber, Sydney; Neate, Nigel; Watts, Julie A.; Noy, Aleksandr; Rawson, Frankie J.
Abstract: Cells modulate their homeostasis through the control of redox reactions via transmembrane electron transport systems. These are largely mediated via oxidoreductase enzymes. Their use in biology has been linked to a host of systems including reprogramming for energy requirements in cancer. Consequently, the ability to modulate membrane redox systems may give rise to opportunities to modulate underlying biology. The current work aims to develop a wireless bipolar electrochemical approach to form on‐demand electron transfer across biological membranes. To achieve this goal, it is shown that by using membrane inserted carbon nanotube porins (CNTPs) that can act as bipolar nanoelectrodes, one can control electron flow with externally applied electric fields across membranes. Before this work, bipolar electrochemistry has been thought to require high applied voltages not compatible with biological systems. It is shown that bipolar electrochemical reaction via gold reduction at the nanotubes can be modulated at low cell‐friendly voltages, providing an opportunity to use bipolar electrodes to control electron flux across membranes. The authors provide new mechanistic insight into this newly describe phenomena at the nanoscale. The results presented give rise to a new method using CNTPs to modulate cell behavior via wireless control of membrane electron transfer. Abstract : Carbon nanotube porins (CNTPs) are used as biomimetic membrane electron transport systems. CNTPs are inserted into lipid membranes, and electric fields are applied inducing transport of electrons across membranes through bipolar electrochemistry. This is demonstrated by extracellular wireless electrochemical reduction of Au + (Aq) to Au(s) at the membrane interface of giant unilamellar vesicles and neuronal cell membranes containing CNTPs.